A new formulation of heat dissipation in a rocking Büttiker-Landauer ratchet model - Mazzitello, Karina Irma (2019)
Thermal ratchets achieve net particle transport through recti cation of thermal uctuations, which arise from one or more heat baths in the system. We propose a new formulation of heat dissipation from the ratchet to the thermal baths, using a rocking Büttiker-Landauer ratchet model. We found that heat transport between the ratchet and the heat baths is related to the effective temperature through the generalization of the uctuation-dissipation theorem for systems far from equilibrium. We showed that the net heat transport between the ratchet and the heat baths is different from Fourier's law and is the sum of two terms which are proportional to the nth power of the difference between the effective temperature of ratchet and the temperature of the baths. The power n depends only on the temperature of the bath, while the thermal conductivity also depends on the ratchet potential. These ndings suggest that anomalous heat dissipation can be a non-equilibrium measure for systems far from equilibrium.